2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34067
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Student Entrepreneurial Failure in Engineering Education

Abstract: Luis Obispo (Cal Poly). He works in the BioMedical Engineering Department and has a joint appointment in the Orfalea College of Business. Before joining Cal Poly, he worked in startup companies in the LED and LED lighting industry. His roles in industry included leading product development teams, business development, and marketing. He received a Ph.D. in Electrical Engineering from UC Santa Barbara, studying with the inventor of the blue and white LED, and an MBA from the University of South Carolina, Moore S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Educators have a responsibility to inform students of the potential risks associated with entrepreneurship, which may include financial losses or psychological distress. While many programs list "learning from failure" or "failing fast" as a possible intended learning outcome, there has been little research on the psychological impact of failure in student entrepreneurial teams (Katona et al, 2020).…”
Section: Findings and Conclusionmentioning
confidence: 99%
“…Educators have a responsibility to inform students of the potential risks associated with entrepreneurship, which may include financial losses or psychological distress. While many programs list "learning from failure" or "failing fast" as a possible intended learning outcome, there has been little research on the psychological impact of failure in student entrepreneurial teams (Katona et al, 2020).…”
Section: Findings and Conclusionmentioning
confidence: 99%
“…With this exposure, it is unknown whether sufficient preparation and education around project/venture failure is occurring to properly equip entrepreneurially minded engineering students to learn and grow from entrepreneurial failure. In fact, previous work has shown that little is done to help students prepare for and respond to entrepreneurial failure beyond some isolated and relatively cursory classroom activities [9]. It's also not clear that these relatively young entrepreneurs define and perceive failure in the same context as is traditionally described in entrepreneurial literature.…”
Section: Introductionmentioning
confidence: 98%